The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.febslet.2011.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in cytochrome bc1: Inter monomer electronic communication?

Abstract: The ubihydroquinone: cytochrome c oxidoreductase, or cytochrome bc1, is a central component of photosynthetic and respiratory energy transduction pathways in many organisms. It contributes to the generation of membrane potential and proton gradient used for cellular energy production (ATP). The three-dimensional structures of cytochrome bc1 indicate that its two monomers are intertwined to form a symmetrical homodimer. This unusual architecture raises the issue of whether the monomers operate independently, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
(69 reference statements)
0
27
0
Order By: Relevance
“…We demonstrated that strains in which the heterodimeric constructs enforced an inter-monomer path could not compete with monomeric function. Although this problem had not been discussed in the earlier papers, in subsequent papers [91, 92] two groups acknowledged that recombination occurred with high frequency in their systems, and addressed the question in greater detail. In a more recent paper [93], the rates reported in isolated heterodimeric complexes constructed so as to enforce the inter-monomer path were <10% those measured in similar constructs with wildtype sequence, - much too slow to be commensurate with the original claims, or with a half-of-sites mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that strains in which the heterodimeric constructs enforced an inter-monomer path could not compete with monomeric function. Although this problem had not been discussed in the earlier papers, in subsequent papers [91, 92] two groups acknowledged that recombination occurred with high frequency in their systems, and addressed the question in greater detail. In a more recent paper [93], the rates reported in isolated heterodimeric complexes constructed so as to enforce the inter-monomer path were <10% those measured in similar constructs with wildtype sequence, - much too slow to be commensurate with the original claims, or with a half-of-sites mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…To a greater or lesser extent, these alternative mechanisms would require re-evaluation of the data that had led to identification in the 1980s of Garland’s modified Q-cycle [2, 5, 2529] as the most economical hypothesis. Rather than repeat the detailed arguments in the previous review, we will focus on developments since then that have been claimed to demonstrate that intermonomer electron transfer occurs at rates compatible with an important role in normal flux [14, 16, 19, 3032]. Does the proposed intermonomer electron transfer represent a challenge demanding a paradigmatic change in our thinking, or a diversion?…”
Section: Monomeric or Dimeric Functionmentioning
confidence: 99%
“…19 We also observed that strains carrying the two-plasmid system formed rare (∼10 −4 ) large Ps + colonies among a population of predominantly small Ps +/− colonies. 19,20 …”
mentioning
confidence: 99%